The effect of system engıneerıng model on school management - Debeş, Gülyüz; Öznacar, Behcet (Journal of the University of Zulia, 2019)
This article emphasizes the necessity and importance of system engineering in the field of education. The problems related to education in the field of system engineering and the necessities in the field of education are discussed. Nowadays, many institutions and organizations have developed systems engineering in order to simplify the projects to be carried out in the field of education for it to be high quality and less costly. In order to meet the needs of the public and private sectors, system engineering is very important and the demand towards it in the academic field is increasing day by day. In this context, the necessary changes to be made in the field of education, inputs and outputs to be done, if any, to reach the solution of the problems or to make improvements are among the aims of the system engineering. This research is done to reveal the opinions of teachers and managers and their past experiences in such cases. Pre-test and post-test were applied in the study and the results were evaluated. The field of system engineering is still young and dynamic and will be recognized more and more over time and will be implemented both in organizations and training.